Erosion Index Analysis for Eastern Ghat High Land Zone of Orissa - Susama sudhishri; U.S.Patnaik (Journal of Soil and Water Conservation, 2022)
The average annual and seasonal rainfall of Eastern Ghat High Land (EGHL) Zone (1970-2001) varies from 1300 to 1900 mm and 1000 to 1600 mm respectively. June and July are the most erosive months in the rainy season. Erosion index during the month from May to September accounts for about 83.7 per cent of annual value. Highest erosion index was observed during the year 1995 and lowest in 1997. The average annual and seasonal erosion index vary from 618.78 to 1061.66 and 388.03 to 945.39 respectively. The linear regression equations were developed between the kinetic energy (KE), Erosion index (EI,), Erosive rain (ER) and total rainfall (P) and El & PI for 5, 10. 15, 30 and 60 minutes duration. Frequency analysis of El, revealed that for annual El, Log- Pearson Type III and for other durations, Extreme Value Type I are the best-fit distributions basing on c2 test. Iso-erodent maps for seasonal and annual erosion index were also developed for EGHL zone for standardizing the conservation practices.